Emergence of Twelver Shiism and ‘The Islamic Movement’ In Nigeria’s North-Central Geo-Political Zone - Adeyemi, Waliyullahi Adeola (The Department of Islamic History and Culture in cooperation with the Center for Islamic History and Culture in Aceh and Malay World Studies (PUSAKA), Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2025)
The spread of Twelver Shiism across the Muslim world owes its origin to the 1979 Iranian revolution led by Āyatullāh Al-Khumaynī. Shiism pervaded the soil of Nigeria afterwards in the early 1980s through the MSSN campus activism in Northern Nigeria spearheaded by Ibrahim El-Zakzaky. The prominent protagonists who kept the Shiite flag aloft were the Lebanese traders in Kano State accompanied by the students in Northern Universities in Nigeria, who saw the success of the Iranian revolution as a harbinger of practicability of theocratic government in Nigeria. While most writers focused on Shiite development in North-Western Nigeria, the paper delved into the discourse on diffusion of Shiism across North-Central Nigeria. The research adopted a historical method to analyse the sporadic spread of Twelver Shiism to Nigeria’s North-Central under the umbrella of the Islamic Movement in Nigeria. Despite the fact that the Shiites in North-Central Nigeria upheld the Twelver doctrines, the Shiites in Okene area of Kogi State do not pay homage to El-Zakzaky. The paper concluded that the former’s indifference to the latter’s superintendence was based on political reasons.